TAKSONOMI BLOOM – REVISI RANAH KOGNITIF (KERANGKA LANDASAN UNTUK PEMBELAJARAN, PENGAJARAN, DAN PENILAIAN) - Ni Nyoman Lisna Handayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Cognitive domain of Bloom’s taxonomy often serves as a framework for categorizing objectives of education, designing tests, and designing curricula. The taxonomy in order covers: (1) knowledge, (2) comprehension, (3) application, (4) analysis, (5) synthesis, and (6) evaluation. The order has been made use more than fifty years as the basis for education objectives, designing tests and curricula. Revision on the taxonomy is done by changing noun in the taxonomy into verb in the revised taxonomy. This is in order to meet education objectives. Such objectives indicate that students will be able to do something (verb) by using something (noun). Revision by Kratwohl and Anderson resulting the taxonomy: (1) remember, (2) understand,(3) apply, (4) analyze, (5) evaluate, and (6) create.Keywords: Revized Bloom’s Taxonomy, Cognitive Domain